2010
DOI: 10.1039/c004113k
|View full text |Cite
|
Sign up to set email alerts
|

Colored noise, folding rates and departure from Kramers’ behavior

Abstract: Recent experiments have shown that, for several proteins, the dependence of folding and unfolding rates on solvent viscosity does not obey Kramers' theory. Such a departure from standard Kramers' behavior is often attributed to the existence of internal friction, related to the structure of a polypeptide chain. In this paper, we propose an entirely different mechanism leading to violation of Kramers' theory. Using the generalized Langevin equation with time-dependent friction and a C(α)-Go model, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…We expected that the increased deviation with the parameters would correspond to an increase in σ; while σ increases with the barrier curvature, it decreases with the solute–solvent coupling and solute size (Figure a–d). Therefore, deviation from KT or memory friction alone, as previously thought, does not correlate with σ.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…We expected that the increased deviation with the parameters would correspond to an increase in σ; while σ increases with the barrier curvature, it decreases with the solute–solvent coupling and solute size (Figure a–d). Therefore, deviation from KT or memory friction alone, as previously thought, does not correlate with σ.…”
Section: Resultsmentioning
confidence: 56%
“…Therefore, the above results, nonzero σ or the fractional value of α in the water bath, indicate that a fit to Ansari’s equation may not provide an estimate of internal friction; rather, it indicates a deviation from Kramers’ behavior only. This deviation has already been shown to depend on the frequency-dependent friction, first by Bagchi and Oxtoby and later by many others. , …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…[2]. It was recently shown that, for several proteins, the dependence of folding and unfolding rates on solvent viscosity does not obey Kramers' theory and thus, indicating the necessity to use colored noise descriptions [3]. These descriptions may be implemented through non-Markovian Langevin equations.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, experiments using laser optical tweezers (LOT) are implemented in order to produce an external force, which induces conformational changes on the structure of RNA or DNA molecules [2][3][4][5][6][7]. The system considered in these works is made up by a RNA hairpin joined at its ends through two appropriate polymeric arms to two polystyrene beads.…”
Section: Introductionmentioning
confidence: 99%